LEADERSHIP AND LEADERSHIP IN MANAGEMENT PSYCHOLOGY. (Conference Zone, 2021)
This article discusses the emergence and development of management psychology. It also discusses the theoretical and practical importance of management psychology in society, focusing on different sociopsychological approaches to management psychology.